2016
DOI: 10.19082/3412
|View full text |Cite
|
Sign up to set email alerts
|

Perceived needs in women with gestational diabetes: A qualitative study

Abstract: IntroductionDiabetes is the most common medical complication of pregnancy. It can be associated with many complications for mother and fetus. Gestational diabetes is also one of the main health issues in Iran. Therefore, the present study is aimed at a deeper understanding of women’s experiences of gestational diabetes and their perceived needs to inform future lifestyle interventions.MethodsThis qualitative content analysis study was carried out in 2015. Participants were pregnant women diagnosed with gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 20 publications
0
17
0
7
Order By: Relevance
“…Some women in this study found their family’s excessive concerns or providing unhealthy meals a challenge and reported that this contributed to them feeling stressed and unable to perform CBG monitoring. A qualitative study of perceived needs in women with GDM found similar findings and indicates the importance for health professionals to increase their awareness for the need of social support for women with GDM [ 70 ]. Other studies including women with borderline GDM and T2DM reiterate this [ 54 , 71 73 ] and recommend, that health professionals as part of clinic appointments need to include discussions about effective strategies to cope with situations that are challenging for women with GDM.…”
Section: Discussionmentioning
confidence: 70%
“…Some women in this study found their family’s excessive concerns or providing unhealthy meals a challenge and reported that this contributed to them feeling stressed and unable to perform CBG monitoring. A qualitative study of perceived needs in women with GDM found similar findings and indicates the importance for health professionals to increase their awareness for the need of social support for women with GDM [ 70 ]. Other studies including women with borderline GDM and T2DM reiterate this [ 54 , 71 73 ] and recommend, that health professionals as part of clinic appointments need to include discussions about effective strategies to cope with situations that are challenging for women with GDM.…”
Section: Discussionmentioning
confidence: 70%
“…Such interventions should be initiated early in pregnancy and continue throughout the pregnancy, as major short-and long-term health consequences for both the mother and the child are likely. • Develop and implement national diabetes plans as well as regional strategies promoting local partnerships with communities and stakeholders [38] • Governments should support the implementation of interdisciplinary care teams, with special regard to the involvement of pharmacists [39] • Improve the transparency of product ingredients using mandatory simple and intuitive nutrition or menu labelling [40] • Set up government food benefit programmes to incentivise the purchase of fruit and vegetables [41] • Support the certification of digital devices and apps to improve access to evidencebased health information [42] • Use narrative and visual messages to improve diabetes awareness [43] • Support interpretative nutrition labelling, like traffic lights, to decrease SSB sales [41] • Strengthen the framing of diabetes as a problem to be tackled on the societal level [44] • Raise taxes on unhealthy products (and consider the liability for adverse health effects of food and beverage products) and reinvest the money in local infrastructure (outdoor gyms and playgrounds) [45] Pregnant women and young families • Screen high-risk groups (elevated risk due to family history, increased BMI) for early detection of GDM [46] as a precondition for lifestyle change • Give advice regarding healthy eating and set activity targets during pregnancy [47,48] • Give advice regarding the benefits of breastfeeding [49] • Employ multimedia communication strategies to increase the widespread knowledge of diabetes risk during pregnancy [50,51] Children and adolescents…”
Section: Pregnant Women and Young Familiesmentioning
confidence: 99%
“…individuals with impaired glucose tolerance or those with low literacy), governments should employ communication strategies based on targeting, the use of multiple media channels [42] and the involvement of an individual's support network, such as family and friends, as well as physicians [92][93][94][95]. Government strategies aiming to decrease the prevalence of risk factors for GDM should employ a broad spectrum of media channels to increase awareness rather than relying solely on the effectiveness of prepregnancy care [50,51]. Accordingly, mass media channels, especially the internet, as well as workshops and symposia accessible to the public are valid sources of information for this group of rather active diabetes information seekers [50].…”
Section: Evidence-based Communication Strategiesmentioning
confidence: 99%
“…For instance, the nutritional advice on a restricted diet of fast foods should also discuss about where a patient can get healthy foods and her related barriers. Moreover, understanding the effects of the dietary advice on not only an individual but also her family members has shown the significant improvement of clinical outcomes [33,34]. This is likely due to family member's additional support.…”
Section: A Personalized Counseling For Gdmmentioning
confidence: 99%